Penilaian Kerusakan Pantai di Kecamatan Teluk Ambon dan Prioritas Penanganannya - Sihombing, Tri Octaviani; Tutkey, Monica R.; Warniyati, Warniyati (Universitas Kristen Maranatha, 2025)
Assessment of Beach Damage in Teluk Ambon Sub-district and Prioritisation of Handling. In the management of coastal areas, the assessment of the level of damage to coastal protective buildings is an initial planning step in controlling, preventing, protecting and restoring damage to land, infrastructure and public infrastructure in coastal areas. Assessment or evaluation of the level of coastal damage is needed to find locations of coastal damage that require immediate action. This research was conducted to assess the level of coastal damage and prioritize the handling of coastal protection buildings along the Teluk Ambon sub-district which consists of 8 districts / villages which are then divided into several segments. Each segment was separated by the estuary or edge of the coastal protection structures under review. This study starts by collecting data on damage to coastal structures, analyzing it, then weighing the level of damage and determining the priority of handling. The assessment was conducted in reference to the Circular Letter of the Minister of Public Works No. 08/SE/M/2010 on Guidelines for Beach Damage Assessment and Prioritization of Handling. The coastal damage parameters analyzed include damage/failure of coastal buildings with EA-2 code. The results showed that there were no beach buildings that suffered very heavy (ASB), very heavy (AB) and heavy (B) damage. Coastal buildings that experienced moderate damage (S) with less priority (D) were located in segment 4b of Laha Village. Coastal structures that suffered minor damage with no priority are in segments 1 to 4 of Hunuth Village, segments 1 to 5 of Poka Village, segments 1 to 3 of Rumah Tiga Village, Segments 1 and 2 of Wayame Village, segments 1 to 8 of Hative Besar Village, segments 1 to 4 of Tawiri Village, and segments 1 to 4a of Laha Village.